MMS observations of electron‐scale filamentary currents in the reconnection exhaust and near the X line. Issue 12 (29th June 2016) - Phan, T. D.; Eastwood, J. P.; Cassak, P. A.; Øieroset, M.; Gosling, J. T.; Gershman, D. J.; Mozer, F. S.; Shay, M. A.; Fujimoto, M.; Daughton, W.; Drake, J. F.; Burch, J. L.; et al.
Abstract: We report Magnetospheric Multiscale observations of macroscopic and electron‐scale current layers in asymmetric reconnection. By intercomparing plasma, magnetic, and electric field data at multiple crossings of a reconnecting magnetopause on 22 October 2015, when the average interspacecraft separation was ~10 km, we demonstrate that the ion and electron moments are sufficiently accurate to provide reliable current density measurements at 30 ms cadence. These measurements, which resolve current layers narrower than the interspacecraft separation, reveal electron‐scale filamentary Hall currents and electron vorticity within the reconnection exhaust far downstream of the X line and even in the magnetosheath. Slightly downstream of the X line, intense (up to 3 μA/m 2 ) electron currents, a super‐Alfvénic outflowing electron jet, and nongyrotropic crescent shape electron distributions were observed deep inside the ion‐scale magnetopause current sheet and embedded in the ion diffusion region. These characteristics are similar to those attributed to the electron dissipation/diffusion region around the X line. Key Points: Demonstrate unprecedented MMS measurements of current density at 30 ms, capable of resolving current layers on electron skin depth scales Evidence for electron‐scale filamentary Hall currents in exhaust and at its boundaries ~70 ion skin depths downstream of the X line Nongyrotropic crescent shape electron distributions in electron current layer embedded in the ion diffusion region near the X line